Sistem Pendukung Keputusan Penetuan E-Commerce Dengan Metode Topsis Bagi Umk Di Area Kota Medan Mengunakan Pembobotan Roc - Nababan, David Juanda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
SPK is an implementation of decision-making theories that have been introduced by sciences such as operations research and management. However, in DSS itself, a method or basis for a decision is needed which is to be established as a reference for an explanatory formula that is relevant to the running of a decision to be reached. A decision support system (DSS) is a decision support system that can assist in handling or solving problems in a company or in a daily environment, in determining a problem we need data that we will take in a company or in an environment. . In writing this is an example of a problem that is happening with the case study of the Best Market Place Application Selection in the city of Medan, therefore the author uses a method that will be able to find alternative data, therefore the author creates a decision support system that will be able to determine the best market place application assessment process in the city of Medan. This decision support system was created using the TOPSIS method with ROC weighting where this method can be used or can be used as a reference in determining a problem because it aims to find out how many of the Best Market Place Application Names in Medan City are Frequently Used, after being tested try to give a weight value to the criteria and it can be modified which aims to find out how many criteria will be added in each criterion that has its own weight value and after that a ranking is made called the ranking can already determine the best application in the city of Medan, namely ( T4) Shopee with a score of 2,219. So because of this it was confirmed or very easy for the team to select in the decision making and was selected as the Best Market Place Application in the city of Medan.